The Dream Merchants - Robbins, Harold, 1916-1997 (New York Pocket Books, 1976)
When Hollywood was young, powerful men and sensual women did whatever they had to in order to get what they wanted. With eleven weeks on The New York Times bestsellers list, this novel of passion and intrigue provides a fascinating look at the early days of the world's most glamorous industry. Johnny Edge, a former carnival barker, schemes and plots his way to the top while Peter Kessler turns his back on a staid life of small-town stability to stake his fortune on the movie business. Beautiful starlet Dulcie Warren is willing to use her sexuality and to play dirty to get to the top, if that's what it takes.
Keywords: Motion picture industry -- California--Los Angeles--Hollywood -- Motion pictures -- American fiction